Control constitucional de los tributos con fines extrafiscales en el perú - Landa Arroyo, César (2013)
Traditionally, it has been understood that taxes have only a collection purpose. Nevertheless, our constitutional tax legal system has allowed the existence of extra tribute taxes, that is, those who pursue “something else” Are they constitutionally legitimate? In this article, and on the basis of thejurisprudence of the Constitutional Court of Peru, the author explains its content and their sustenance, as well as its limits: the principles of Constitutional Tax Law.